Enhancing Peer Learning through Online Placements for Health and Social Care Professions - Taylor, Lisa; Salmon, Gilly (International Journal of Practice-based Learning in Health and Social Care, 2021)
This article reports on the innovative design and the delivery of an online placement for university students, in response to the suspension of face-to-face placements due to COVID-19 restrictions in April 2020. A high quality, evidence-based and pedagogically sound experience was built, delivered and reviewed. The online placement not only met the professional standards and demonstrated equivalence in achieving placement learning outcomes, compared to traditional face to face placements, but also offered emergent benefits. The online placement showed enhanced peer learning and improved professional reasoning development by the students. In view of the interest and need for alternative placements, online placements were explored further, contextualised and built into a model which came to be known as Peer-Enhanced E-Placement (PEEP). Throughout 2020, and into 2021, the ‘logjam’ of increased student numbers and reduced placements, dramatically increased the interest in alternative placement learning and the PEEP model. A PEEP professional development acquisition experience was developed and piloted, to disseminate, scale and contextualize the approach by health and social care teams. Feedback from the pilot acquisition experiences indicated that the participants were able to design and implement PEEPs in their own contexts with their students. The scaling up and roll out of the PEEP acquisition experiences now extends to over fifteen professions. Conclusions include that the PEEP model offers a viable, acceptable and successful online practice-based learning option for health and social care students, achieving equivalence in placement learning outcomes and enhanced peer learning.